1955
DOI: 10.1107/s0365110x55001679
|View full text |Cite
|
Sign up to set email alerts
|

On the relations between structure and morphology of crystals. II

Abstract: The characteristic features of S-faces (stepped faces, i.e. faces parallel to one periodic bond chain only) are further developed. After giving some definitions, a discussion follows of the factors determining the morphological importance of S-faces. The conclusion is drawn that the development of S-faces in a particular zone can be represented by an addition scheme of indices and that an S-face is the more important, the greater the relative strength of the bonds in the periodic bond chain to which it is para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
439
0
12

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 647 publications
(461 citation statements)
references
References 0 publications
10
439
0
12
Order By: Relevance
“…6). Harvill and Roy (1966) have reported that the SnO2 crystals grown hydrothermal ly from a KOH solvent show only (110) and (101) faces, which are in accordance with the prediction of Hartman's theory (Hartman and Perdok (1955)). According to Hartman (1966) the (110) and (101) faces are a F-face; the (100), an S-face; and the (111), a K-face in rutile type oxides such as SnO2.…”
supporting
confidence: 58%
“…6). Harvill and Roy (1966) have reported that the SnO2 crystals grown hydrothermal ly from a KOH solvent show only (110) and (101) faces, which are in accordance with the prediction of Hartman's theory (Hartman and Perdok (1955)). According to Hartman (1966) the (110) and (101) faces are a F-face; the (100), an S-face; and the (111), a K-face in rutile type oxides such as SnO2.…”
supporting
confidence: 58%
“…In this way the crystal graph go back to the morphological crysreal crystal structure is reduced to a crystal graph, tallographic theory of Hartman and Perdok i.e. a set of an infinite number of points with [12][13][14][15].In this theory the concept of Periodic relations (bonds) between these points. The crystal Bond Chain (PBC) plays an essential role.…”
Section: Introductionmentioning
confidence: 99%
“…Hartman's periodic bond chain (PBC) 23,24 theory (also called 'Hartman -Perdok-roughening-connected net') 25 classifies the crystal faces in three groups: F (flat) faces where the surface structure contains, strong intermolecular bonds (PBC) between atoms, ions or molecules of the crystal at least. In two non-parallel directions; S (stepped) faces corrugated, in one direction and with only one strong bond direction, and K (kinked) with no PBC, that are irregular with growth sites of vertex or edge types.…”
Section: X-ray Powder Diffraction Diagram Of Compoundmentioning
confidence: 99%